1977
DOI: 10.1104/pp.59.5.970
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Changes in Anacystis nidulans Induced by Chilling

Abstract: When Anacystis nidulans, strain TX 20 was grown at 39 C, then rapidly chilled to 0 C, a pigment with a carotenoid-ike spectrum was bleached. This effect was not seen when ceUs which had been grown at 25 C were chiRled. The effect seen in 39 C-grown ceUs was not reversible except under extreme conditions such as beating to near boiling for several minutes. Bleaching could be prevented by prior exposure of cells to glutaraldehyde, but could not be reversed by glutaraldehyde treatment following chiUling. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In agreement with previous studies (3,4,13), we found that the absorption spectrum of the alga cells is greatly influenced by chilling pretreatment. An absorption increase occurs at 390 nm, which has been attributed to a conformational change or an aggregation of the zeaxanthin in the membrane, due to a lipid phase transition (13,25,26).…”
Section: Methodssupporting
confidence: 81%
“…In agreement with previous studies (3,4,13), we found that the absorption spectrum of the alga cells is greatly influenced by chilling pretreatment. An absorption increase occurs at 390 nm, which has been attributed to a conformational change or an aggregation of the zeaxanthin in the membrane, due to a lipid phase transition (13,25,26).…”
Section: Methodssupporting
confidence: 81%
“…strains PCC 7942 and PCC 6301 (previously referred to as Anacystis nidulans) (4,8,19,23,34,36). Figure 5 shows that the phase transition of the membrane lipids of the PAM cells first became apparent at 10ЊC and ceased at 2ЊC, with a mid-point temperature at about 6ЊC.…”
Section: Resultsmentioning
confidence: 99%
“…strain PCC 6301 (previously termed A. nidulans) is caused by the transition of the lipid phase of plasma membranes from the liquid crystalline state to the phase-separated state (19). Since changes in the absorption spectra of carotenoids in intact cells are a good indicator of changes in the lipid phase in Synechococcus (4,8,19,23,34,36), we were able to determine the profiles of temperature dependence of the lipid phase of the plasma membranes in PAM and PAMCOD cells. The results demonstrated that the phase transition of the plasma membranes of PAMCOD cells was shifted toward lower temperatures, compared with that of PAM cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They seem to possess an evolutional position between bacteria and plants. Therefore, the chilling susceptibility of the blue-green algae can be a link which connects chilling injury and cold shock.A number of studies have been done to reveal that a blue-green alga, Anacystis nidulans, is susceptible to chilling (1,3,4,8,20 Kratz and Myers (9) bubbled with air enriched by 1% CO. Continuous illumination light with an intensity of 6,000 lux was provided from incandescent lamps.…”
mentioning
confidence: 99%
“…A number of studies have been done to reveal that a blue-green alga, Anacystis nidulans, is susceptible to chilling (1,3,4,8,20). When the algal cells are exposed to low temperatures near 0 C, the viability of cells declines (20), the photosynthetic 02 evolution, 'This work was supported by Grant- 'To whom reprint requests should be addressed.…”
mentioning
confidence: 99%